GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 221 species occurrences available in GBIF matching the query: TaxonKey: Tortula mucronifolia Schwaegrichen, 1811 Geometry: POLYGON((7.734374 81.093213,7.734374 36.597889,54.84375 36.597889,54.84375 81.093213,7.734374 81.093213)) or POLYGON((-23.90625 66.231457,-23.90625 34.307143,36.5625 34.307143,36.5625 66.231457,-23.90625 66.231457)). The dataset includes 221 records from 17 constituent datasets: 1 records from Bryophyte herbarium, Tromsø Museum. 4 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 12 records from BioFokus. 8 records from Artdata. 86 records from Bryophyte herbarium, NTNU University Museum. 1 records from Bryophyte herbarium, Oslo (O). 4 records from INPN - Données flore des CBN agrégées par la FCBN. 10 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 36 records from Herbarium (ICEL). 1 records from Herbarium (AMNH). 5 records from Biologiezentrum Linz. 1 records from Herbarium of Umeå University (UME). 29 records from Mosses (S). 6 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1 records from Briòfits d'Andorra. 13 records from Lund Botanical Museum (LD). 3 records from Norwegian Species Observation Service. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences